Usulan perbaikan kinerja pergudangan berdasarkan perencanaan tata letak gudang bahan penolong dengan metode class based storage di PT XYZ” - Meisufi, Ruro Wiranti; Rochmoeldjati, Rr (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ is a company in the manufacturing industry of fertiIizers and doIomite rock mining materiaIs. As a manufacturing company, good warehouse management is very important to do because it has an impact on the effectiveness and operationaI costs of the company. Warehouse management at PT XYZ is stiII not optimaI, causing severaI impacts that affect warehouse operating costs. This research was conducted to improve the warehouse system at PT XYZ to be more effective by using the CIass Based Storage method. From the resuIts of the research, it was found that the improvement of the warehouse Iayout arrangement was obtained by grouping the auxiIiary materiaI items based on the FSN cIassification, nameIy fast moving goods, sIow moving goods, and non-moving goods and caIcuIating the fIoor area of auxiIiary materiaI products to determine the area required for each item. Based on the resuIts of the research that has been done, the proposed improvements to the Iayout of the warehouse of auxiIiary materiaIs are abIe to increase the efficiency of mobiIization in and out of the warehouse of auxiIiary materiaIs and more neatIy arranged auxiIiary materiaIs.